PENERAPAN KENDALI MANUAL DAN OTOMATIS PADA MINIATUR CRANE BERBASIS PLC ZELIO - Fitriady (J-Innovation, 2018)
Crane is one of mechanical tools that generally used in industry to lift and move material or product from one place to another. Conventionally, crane operated manually by operator. However, along with the growth of technology, it is expected to operate the crane automatically also in order to do repetitive works as efficiencies. Automatization in industry is growth together with modern industrial development where control systems have important role in improvement of an industry. Therefore, in this study develops a miniature crane with PLC Zelio SR3B261BD as a controller to applied manual mode and automatic mode program in order to lift and move material by crane manually or automatically.